2010
DOI: 10.1002/qua.22662
|View full text |Cite
|
Sign up to set email alerts
|

The localized electrons detector as an ab initio representation of molecular structures

Abstract: The local single particle momentum is proposed as a localized-electrons detector (LED) that provides a direct three-dimensional representation of bonding interactions in molecules. It is given exclusively in terms of the electron density and its gradient. We show that the graphical representation of bonding interactions given by LED is consistent with the local curvatures of the electron density as given by the eigenvalues of the Hessian matrix, according to a local symmetry classification of the critical poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 28 publications
1
59
0
Order By: Relevance
“…19 Otherwise, a localized-electrons detector (LED) function defined in the quantum mechanics local moment representation and given exclusively in terms of the electron density and its gradient was recently proposed. 20,21 Using this LED function, an opposite pattern of the electron density localization for typical insulator cubic ceramic and good conductors transition metal materials, corroborating the Kohn conclusion, was been recently reported. 22 It was found that, for the elemental ceramic materials, the zone of low electron localization is very small and show areas containing the BCPs and the remainder CPs in separates regions of the space: the electrons are localized in separate areas and cannot move freely through the material.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…19 Otherwise, a localized-electrons detector (LED) function defined in the quantum mechanics local moment representation and given exclusively in terms of the electron density and its gradient was recently proposed. 20,21 Using this LED function, an opposite pattern of the electron density localization for typical insulator cubic ceramic and good conductors transition metal materials, corroborating the Kohn conclusion, was been recently reported. 22 It was found that, for the elemental ceramic materials, the zone of low electron localization is very small and show areas containing the BCPs and the remainder CPs in separates regions of the space: the electrons are localized in separate areas and cannot move freely through the material.…”
Section: Introductionsupporting
confidence: 76%
“…LED isocontours show the same kind of symmetries 21 around the bond critical points that are given by the Laplacian of the electron density. Thus, it can show 3D-dimensionally the different kinds of bonding interactions identified by the topological analysis: the closed shell and the shared interactions.…”
Section: The Localized Electrons Detector Led Functionmentioning
confidence: 80%
See 2 more Smart Citations
“…No remarkable change was noticed with respect to the standard calculation. To investigate the presence and nature of halide-PVA interactions, two different approaches were used: (1) topological analysis based on Bader's atoms in molecules (AIM) theory [21][22][23] and (2) the covalent interaction (NCI) index combined with the second derivative of the reduced density gradient along the second main axis of variation [24][25][26][27]. B3LYP[+GD3BJ] geometries and electron densities were used for this purpose.…”
Section: Computational Detailsmentioning
confidence: 99%